Position paper of the Polish Society of Cardiothoracic Surgeons and the Heart Rhythm Association of the Polish Society of Cardiology on atrial fibrillation hybrid management - Kowalewski, Mariusz; Farkowski, Michał; Batko, Jakub; Ogorzelec, Natalia; Zembala, Michał; Kowalski, Oskar; Aboul-Hassan, Sebastian S.; Płaksej, Rafał; Buchta, Piotr; Hirnle, Grzegorz; Jastrzębski, Marek; Wojdyła-Hordyńska, Agnieszka; et al. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2025)
This position paper, jointly authored by the Polish Society of Cardiothoracic Surgeons and the Heart Rhythm Association of the Polish Society of Cardiology, defines the role of hybrid approaches in the treatment of cardiac arrhythmias, particularly atrial fibrillation. We present a rationale for integrating epicardial and endocardial ablation strategies, summarize current evidence, and advocate for multidisciplinary planning, including arrhythmia treatment during cardiac surgery for other indications and atrial fibrillation treatment as a stand-alone procedure. The paper highlights the importance of minimally invasive approaches, the need for heart team-based planning, structured curricula, and postoperative referral pathways for comprehensive management of atrial fibrillation and non-atrial fibrillation arrhythmias.